Access and Adoption of Hybrid Seeds: Evidence from Uganda. (21st June 2019) - Axmann, Nikolaus; Fischer, Torben; Keller, Kevin; Leiby, Kevin; Stein, Daniel; Wang, Paul
Abstract: Adoption of hybrid seeds remains low in many low-income countries. We conduct a field-experiment designed to measure the effect of offering hybrid maize seeds for purchase during a time when potential customers have high liquidity. Working with a large buyer of agricultural commodities in Northern Uganda, we randomly offer smallholder farmers the opportunity to purchase certified hybrid maize seeds at the same time as they visit the buyers' stores to sell crops from a previous harvest. 16% of those offered purchase hybrid seeds, and average adoption of hybrid maize among those offered increases by 8 percentage points compared to a control group who does not receive the offer. Among those who accept the offer, we see an increase in the propensity to plant hybrid maize of 50 percentage points. This effect is more pronounced for female farmers than for their male counterparts. Our findings suggest that providing access to certified agricultural inputs at the place and time of post-harvest sales is a promising strategy to increase input usage.